Amonification of corn stover (Zea mays L) with three levels of urea to improve its digestibility - Castellanos, Shirley (2017)
The aim of this study was to evaluate the effect of urea (46% N) on the nutritional quality of corn stover from the areas of Chilampa, La Villa, Miramar and La Querencia of the Cattle Association Irrigación San Felipe, located in Huaura, Lima (Peru). Three levels of urea (0, 3 and 6%) in an aqueous solution over a period of 14 days were applied and the forage was stored in sealed plastic bags. The variables evaluated were crude protein content (CP%), neutral detergent fiber content (NDF%), in vitro digestibility of dry matter (IVDDM%), in vitro digestibility of neutral detergent fiber (IVNDFD%), intake potential of dry matter (%PV DM) and relative feed value (RFV). Randomized complete block design with three replications was used. The results for 0, 3 and 6% urea were: 84.66, 70.01 and 67.78% DM; 5.08, 8.02 and 12.92% CP; 77.31, 76.89 and 74.84% NDF; 59.90, 61.17 and 66.59% IVDMD; 48.15, 50.97 and 55.41% IVNDFD; 1.55, 1.56 and 1.60% potential intake of dry matter; and 72.09, 74.03 and 82.81 FRV respectively. The results of the analysis showed no difference between the source of corn stover or for IVNDFD between the urea levels; however, there was significant difference (p<0.05) of CP content, NDF, IVDMD, potential intake of dry matter and the FRV between the levels of urea.